Modeling of Gough Stewart Robot Manipulator Inverse Kinematics by Using MSC ADAMS Software (Journal of University of Babylon for Engineering Sciences, 2018)
The Gough Stewart Robotic manipulator is a parallel manipulator with six-degree of freedom, which has six equations of inverse and forward with six variables. This paper model of the Gough Stewart has been built into the MSC ADAMS software and its motion based on the inverse equations of the Stewart. Then compare the obtained results from the software with the results, which obtained from theoretical model.